Answer:
![x= (2 \pm i√(17))/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csoxg5y471c2a6olxo77ru2zvpoq9uvjdn.png)
Explanation:
A complex number is the sum of a real number and an imaginary number.
An imaginary number is a non-zero real number multiplied by the imaginary unit
.
![i=√(-1) \implies i^2=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/o6fszg75lrhdlpavotjdx3o2o9i4mfqwit.png)
For example:
- 5
is an imaginary number (and its square is -25) - 5 + 5
is a complex number
Quadratic Formula
![x=(-b \pm √(b^2-4ac) )/(2a)\quad\textsf{when }\:ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/physics/high-school/srcbg1ukkzuvprrhg8mwvjtfb23umv2fbh.png)
Given quadratic equation:
![-3x^2+4x-7=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/jlavchd6qbr1prns6bpqhuiib84weiodwu.png)
Therefore:
![a=-3, \quad b=4, \quad c=-7](https://img.qammunity.org/2023/formulas/mathematics/high-school/2ho6bjyjhr5bmeow2o7nerrt1i5yygdtbs.png)
Inputting these values into the quadratic formula:
![\begin{aligned}\implies x & =(-4 \pm √(4^2-4(-3)(-7)))/(2(-3))\\\\ & = (-4 \pm √(-68))/(-6)\\\\ & = (-4 \pm √(4 \cdot -17))/(-6)\\\\ & = (-4 \pm √(4)√(-17))/(-6)\\\\ & = (-4 \pm 2√(-17))/(-6)\\\\ & = (2 \pm √(-17))/(3)\\\\ & = (2 \pm √(-1 \cdot 17))/(3)\\\\ & = (2 \pm √(-1)√(17))/(3)\\\\ & = (2 \pm i√(17))/(3)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/4vp0lploqi23incmxsdep035unvbkgj7s1.png)
Therefore, the solutions to the given quadratic equation are complex numbers as they include the imaginary number
.